On the solution and Ulam-Hyers-Rassias stability of a Caputo fractional boundary value problem - Luís P. Castro; Anabela S. Silva (Mathematical Biosciences and Engineering, 2022)
In this paper, we investigate a class of boundary value problems involving Caputo fractional derivative $ {{}^C\mathcal{D}^{α}_{a}} $ of order $ α \in (2, 3) $, and the usual derivative, of the form